Features of Anesthesiologists-Reanimatologists’ Emotional States in Different COVID-19 Pandemic Periods in Russia - Korehova, Maria; Kirov, Mikhail; Novikova, Irina; Soloviev, Andrey; Golubeva, Elena (European Journal of Mental Health, 2022)
Introduction: The COVID-19 pandemic is one of the most stressful events in recent times. Medical professionals, including anesthesiologists-reanimatologists, suffered the main blow in this difficult and stressful environment.Aims: This study aimed at identifying the features of anesthesiologists-reanimatologists’ emotional states in different COVID-19 pandemic periods.Methods: The study was conducted through an anonymous questionnaire among anesthesiologists-reanimatologists in two periods. In the First stage – which was carried out in May 2020 (during the first COVID-19 pan¬demic wave) – 58 anesthesiologists-reanimatologists in the Arkhangelsk region took part. During the Second segment – which took place in October 2020 (in the second COVID-19 pandemic wave) – 43 anesthesiologists-reanimatologists were examined. Repeated questioning was carried out among the same participants.Results: In October 2020, compared to May, the number of doctors who noted a high intensity of professional activity increased. Regardless of the study period, one-third of the subjects experienced constant pronounced anxiety. Anesthesiologists-reanimatologists, whose professional activity was directly related to the patients in COVID-19 care, noted a poorer emo¬tional state more frequently in October, accompanied by anxiety, depressed mood, irritability and a high burnout level, which may indicate a depletion of internal resources in this group.Conclusions: The study results showed that for anesthesiologists-reanimatologists, a further depletion of emotional resources accompanied the second pandemic wave. The anesthesiologists-reanimatologists’ emotional state was mediated by a number of social and gender factors, as well as specific labor organization features.